2021
DOI: 10.3390/idr13010016
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the COVID-19 Lockdown on Dengue Transmission in Malaysia

Abstract: We aim to investigate the effect of large-scale human movement restrictions during the COVID-19 lockdown on both the dengue transmission and vector occurrences. This study compared the weekly dengue incidences during the period of lockdown to the previous years (2015 to 2019) and a Seasonal Autoregressive Integrated Moving Average (SARIMA) model that expected no movement restrictions. We found that the trend of dengue incidence during the first two weeks (stage 1) of lockdown decreased significantly with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…The drastic measures imposed by the Sri Lanka government regarding COVID-19 outbreaks help the reduction of dengue hospitalisations. An identical pattern is also found during the first five phrases COVID-19 lockdown in Malaysia (Ong et al, 2021). A vector autoregression component (VAR; Spencer, 1993) can be added to our current setup to incorporate lagged effect dynamically from other variables.…”
Section: Discussionsupporting
confidence: 67%
“…The drastic measures imposed by the Sri Lanka government regarding COVID-19 outbreaks help the reduction of dengue hospitalisations. An identical pattern is also found during the first five phrases COVID-19 lockdown in Malaysia (Ong et al, 2021). A vector autoregression component (VAR; Spencer, 1993) can be added to our current setup to incorporate lagged effect dynamically from other variables.…”
Section: Discussionsupporting
confidence: 67%
“…Reports on the impact of COVID-19 containment measures on the incidence of dengue have been variable, with increases in dengue incidence observed in Thailand and Singapore [ 20 , 21 ] and a decrease in Malaysia [ 15 ]. Data for the second quarter of 2020 suggested that the incidence of dengue decreased in Sri Lanka during that period of the COVID-19 pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extension of ARIMA that supports the direct modeling of the seasonal component of the series is termed the Seasonal Autoregressive Integrated Moving Average model or SARIMA. The SARIMA model takes overall trends as well as seasonal changes in disease incidence into consideration [ 15 ]. Dengue incidence is seasonal and principally associated with rainfall in Sri Lanka [ 5 – 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of India found that the immature density of Aedes mosquito drastically increased during the COVID-19 lockdown due to paused vector control programs [4], and an increased density of vectors was also reported in Malaysia during the COVID-19 lockdown, which has led to increased dengue incidence [5]. During the lockdowns, when human movement is limited to and around own homes, perversely, human-vector contact may be enhanced, resulting in an increased risk of exposure and virus transmission.…”
mentioning
confidence: 99%